Assessment of Axillary Lymph Nodes for Metastasis on Ultrasound Using Artificial Intelligence. (November 2021) - Tahmasebi, Aylin; Qu, Enze; Sevrukov, Alexander; Liu, Ji-Bin; Wang, Shuo; Lyshchik, Andrej; Yu, Joshua; Eisenbrey, John R.
The purpose of this study was to evaluate an artificial intelligence (AI) system for the classification of axillary lymph nodes on ultrasound compared to radiologists. Ultrasound images of 317 axillary lymph nodes from patients referred for ultrasound guided fine needle aspiration or core needle biopsy and corresponding pathology findings were collected. Lymph nodes were classified into benign and malignant groups with histopathological result serving as the reference. Google Cloud AutoML Vision (Mountain View, CA) was used for AI image classification. Three experienced radiologists also classified the images and gave a level of suspicion score (1–5). To test the accuracy of AI, an external testing dataset of 64 images from 64 independent patients was evaluated by three AI models and the three readers. The diagnostic performance of AI and the humans were then quantified using receiver operating characteristics curves. In the complete set of 317 images, AutoML achieved a sensitivity of 77.1%, positive predictive value (PPV) of 77.1%, and an area under the precision recall curve of 0.78, while the three radiologists showed a sensitivity of 87.8% ± 8.5%, specificity of 50.3% ± 16.4%, PPV of 61.1% ± 5.4%, negative predictive value (NPV) of 84.1% ± 6.6%, and accuracy of 67.7% ± 5.7%. In the three external independent test sets, AI and human readers achieved sensitivity of 74.0% ± 0.14% versus 89.9% ± 0.06% ( p  = .25), specificity of 64.4% ± 0.11% versus 50.1 ± 0.20% ( p  = .22), PPV of 68.3% ± 0.04% versus 65.4 ± 0.07% ( p  = .50), NPV of 72.6% ± 0.11% versus 82.1% ± 0.08% ( p  = .33), and accuracy of 69.5% ± 0.06% versus 70.1% ± 0.07% ( p  = .90), respectively. These preliminary results indicate AI has comparable performance to trained radiologists and could be used to predict the presence of metastasis in ultrasound images of axillary lymph nodes.